PRO SELF PAIN CONTROL UNTUK MENURUNKAN NYERI PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI - Tuti Suprapti; Ade Tika Herawati; Sumbara Sumbara (NHM PRESS, 2022)
Cancer is a destructive disease that infiltrates into other tissues through lymph vessels and blood vessels. One of the actions taken is surgery and chemotherapy, one of the efforts to deal with non-pharmacological pain is pro self paint control. The purpose of the study was to identify pain and the effectiveness of Pro Self Pain Control. The research method uses a pre-experiment without a control one group pre-test – post-test design. The population is cancer patients undergoing chemotherapy at the Bandung Cancer Society Shelter House. The sampling technique used purposive sampling, with a sample of 47 people for two weeks. The results of the study were 97.9 pain in the category of minor pain with statistical test results obtained p-value 0.000 < from alpha value (0.05). The self pain control method of pain, namely training skills in recognizing pain, using drugs as well as mentoring and monitoring is carried out for 2 weeks. Patients will be given a pain pocket book for pain monitoring at home. Furthermore, home visits were made in the first and second weeks. The patient will receive a call for monitoring in the first and second weeks. There is a significant effect before and after giving Pro Self Pain Control and after it is effective and can be used as an alternative to reduce pain